Synthesis and Antiproliferative Activities of OSW‐1 Analogues Bearing 2"‐O‐p‐Acylaminobenzoyl Residues†. Issue 10 (20th July 2020) - Sun, Lijun; Zhu, Di; Beverborg, Laura Olde Groote; Wang, Ruina; Dang, Yongjun; Ma, Mingming; Li, Wei; Yu, Biao
Abstract : A library of OSW‐1 analogues bearing 2"‐ O ‐ p ‐acylaminobenzoyl residues were synthesized, and some compounds showed extremely potent antiproliferative activities and could be used as fluorescent probes. Summary of main observation and conclusion: OSW‐1 is a well‐known natural saponin with potent antitumor activities. We have designed and prepared a small library of 22 OSW‐1 analogues with a variety of p ‐acylamino‐benzoyl groups installed at C2" of the xylose residue, wherein a regioselective (1→3)‐glycosylation of arabinoside 3, 4‐diol has been achieved by manipulation of the protecting groups on the imidate donors. Bioassays lead to new structure‐activity relationships as well as two applicable fluorescent probes, which are found to localize to lysosomes in HeLa cells and could be used in further antitumor mechanism studies of OSW‐1 in living cells.